If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = s(s + 3) Reorder the terms: 0 = s(3 + s) 0 = (3 * s + s * s) 0 = (3s + s2) Solving 0 = 3s + s2 Solving for variable 's'. Remove the zero: -3s + -1s2 = 3s + s2 + -3s + -1s2 Reorder the terms: -3s + -1s2 = 3s + -3s + s2 + -1s2 Combine like terms: 3s + -3s = 0 -3s + -1s2 = 0 + s2 + -1s2 -3s + -1s2 = s2 + -1s2 Combine like terms: s2 + -1s2 = 0 -3s + -1s2 = 0 Factor out the Greatest Common Factor (GCF), '-1s'. -1s(3 + s) = 0 Ignore the factor -1.Subproblem 1
Set the factor 's' equal to zero and attempt to solve: Simplifying s = 0 Solving s = 0 Move all terms containing s to the left, all other terms to the right. Simplifying s = 0Subproblem 2
Set the factor '(3 + s)' equal to zero and attempt to solve: Simplifying 3 + s = 0 Solving 3 + s = 0 Move all terms containing s to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + s = 0 + -3 Combine like terms: 3 + -3 = 0 0 + s = 0 + -3 s = 0 + -3 Combine like terms: 0 + -3 = -3 s = -3 Simplifying s = -3Solution
s = {0, -3}
| -0.2d-1=12 | | 9=3+9/3 | | 4(-7x+7)=56 | | 3a+3-3a-2=15 | | 2s+16=4s | | 2x+2=3+x | | x^4-8x^3+24x^2-41x+18=0 | | A=26x-x^2 | | 3x/8=450 | | h=-16t^2+24t+7 | | 2x/5=16 | | 1x/6=15 | | -2.33r-2=3 | | 0=-5x-x^2+24 | | x/16=5 | | .58333333k=1 | | 3(a+1)=19-5a | | -3d+14=23 | | -14*3+(-9)-(-4)*2= | | -.6=-.7x | | n-27=11 | | 144a^2-49b^2=0 | | -9=17-.6666666x | | 12-y=4*3-12 | | x/0.2=10 | | 24x^2=-12x | | 3s^2+11s+10=0 | | x/6=1 | | -13-0.25h=7 | | 7m-3-2m=27 | | 1.33x+3=-1 | | 2.66s=-9+7 |